Deciphering the Role of Multiple Thioredoxin Fold Proteins of Leptospirillum sp. in Oxidative Stress Tolerance - González, Daniela (Int J Mol Sci, 2020)
Thioredoxin fold proteins (TFPs) form a family of diverse proteins involved in thiol/disulfide exchange in cells from all domains of life. Leptospirillum spp. are bioleaching bacteria naturally exposed to extreme conditions like acidic pH and high concentrations of metals that can contribute to the generation of reactive oxygen species (ROS) and consequently the induction of thiol oxidative damage. Bioinformatic studies have predicted 13 genes that encode for TFP proteins in Leptospirillum spp. We analyzed the participation of individual tfp genes from Leptospirillum sp. CF-1 in the response to oxidative conditions. Genomic context analysis predicted the involvement of these genes in the general thiol-reducing system, cofactor biosynthesis, carbon fixation, cytochrome c biogenesis, signal transduction, and pilus and fimbria assembly. All tfp genes identified were transcriptionally active, although they responded differentially to ferric sulfate and diamide stress. Some of these genes confer oxidative protection to a thioredoxin-deficient Escherichia coli strain by restoring the wild-type phenotype under oxidative stress conditions. These findings contribute to our understanding of the diversity and complexity of thiol/disulfide systems, and of adaptations that emerge in acidophilic microorganisms that allow them to thrive in highly oxidative environments. These findings also give new insights into the physiology of these microorganisms during industrial bioleaching operations.